Wavelet analysis of inclusive ⁴He(e,e′) spectrum and missing energy spectrum in reaction ¹²С(γ,p)¹¹В - Omelaenko, A.S. (Вопросы атомной науки и техники, 2004)
We demonstrated that the standard contour plot of the wavelet transform with wavelet “Mexican Hat” of the inclusive ⁴He(e,e′) spectrum and missing energy spectrum in reaction ¹²C(γ,р)¹¹B does not give reliable visual indication of the maxima in experimental spectra. We used the scale disconvolution of the initial spectra to construct more informative image in the energy-scale plane.